THE ROLE OF ISLAMIC CONFERENCE ORGANIZATIONS (OIC) IN THE IMPLEMENTATION OF ISLAMIC TOURISM IN MUSLIM COUNTRIES - Muhd Kharrazi (Awang Long Law Review, 2022)
Islamic tourism is defined as a tourist trip aimed at providing tourist services and facilities for Muslim tourists in accordance with Islamic principles. There are several terms used in addition to Islamic Tourism, namely Halal Tourism, Sharia Tourism, Muslim-Friendly Tourism. Meanwhile, the Global Muslim Travel Index as an institution that focuses on developing world halal tourism explains that halal tourism is tourism that is carried out in accordance with Islamic principles with the aim of providing friendly facilities and services to Muslim tourists. The problem is the role of the Organization of the Islamic Conference (OIC) in the implementation of Islamic Tourism in Muslim countries. The research method is normative juridical research. The conclusion is that the role of the Organization of the Islamic Conference (OIC) in the application of Islamic Tourism in Muslim countries can be concluded with sharia tourism which has been introduced since 2000 from the discussion of the meeting of the Organization of the Islamic Conference (OIC). Sharia tourism is a tourist demand based on the lifestyle of Muslim tourists during the holidays. In addition, sharia tourism is tourism that is flexible, rational, simple and balanced. This tourism aims to motivate tourists to get happiness and blessings from Allah SWT. Halal tourism is an adoption of non-Organization of Islamic Conference (OIC) countries which see the great potential of Muslim growth around the world. Halal tourism was created to accommodate the needs of worship for Muslims in non-OIC countries, such as the provision of places of worship (mushola) and halal restaurants. Countries that are quick to seize the opportunity of this Muslim-friendly tourism service are Thailand, Japan, Singapore, Korea, Australia, New Zealand, UK, France, Malaysia, and many other countries.